2006
DOI: 10.1002/adfm.200500390
|View full text |Cite
|
Sign up to set email alerts
|

Perfect Bi4Ti3O12 Single‐Crystal Films via Flux‐Mediated Epitaxy

Abstract: Excellent crystallinity of material films and atomic control of their surface/interface, sufficient for the realization of their optimal physical properties, are technological premises for modern functional‐device applications. Bi4Ti3O12 and related compounds attract much interest as highly insulating, ferroelectric materials for use in ferroelectric random‐access memories. However, it has been difficult thus far for Bi4Ti3O12 films to satisfy such requirements when formed using vapor‐phase epitaxy, owing to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 28 publications
1
34
0
1
Order By: Relevance
“…In the FME method, an oxide flux on the surface of the film plays a key role in improving the crystallinity of complex oxide films. 13 The vapor ablated from the target material by a pulsed laser meets the flux on the surface of the substrate, diffuses into the liquid intermediate phase and finally solidifies on a predeposited seed layer. The liquid phase ͑flux͒ prevents direct deposition of the vapor phase on the solid surface and improves crystallinity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the FME method, an oxide flux on the surface of the film plays a key role in improving the crystallinity of complex oxide films. 13 The vapor ablated from the target material by a pulsed laser meets the flux on the surface of the substrate, diffuses into the liquid intermediate phase and finally solidifies on a predeposited seed layer. The liquid phase ͑flux͒ prevents direct deposition of the vapor phase on the solid surface and improves crystallinity.…”
mentioning
confidence: 99%
“…Compared to pulsed laser deposition ͑PLD͒, in the FME method, there is enhanced diffusion of the surface atoms in the flux above the quasimelting temperature ͑ϳ0.5T m ͒, which leads to film growth in equilibrium even at high growth rates. [13][14][15] In this work, BFO thin films were grown on SrRuO 3 ͑SRO͒ buffered ͑001͒ oriented SrTiO 3 ͑STO͒ substrates by standard PLD and by FME for comparison. We ablated a 10% Bi excess Bi 1.1 FeO 3 target with a KrF excimer laser ͑ = 248 nm͒ at 650°C and 20 mTorr oxygen partial pressure.…”
mentioning
confidence: 99%
“…2(d). TEM results verified that this film had many out-of-phase boundaries [5]. Moreover, the secondary ion mass spectroscopy (SIMS) measurements showed that a high deficiency of Bi was observed, resulting in high leakage current densities, in the range of 10 −3 -10 −4 A/cm 2 .…”
Section: Flux-mediated Epitaxy Using Bi Oxide Self-fluxmentioning
confidence: 71%
“…One of the possible solutions is to replace the standard thin film fabrication process of these materials for a process using the flux materials as in the bulk fabrication process of single crystals. We have developed a method and named it as "flux-mediated epitaxy" [3][4][5]. This flux-mediated epitaxy is characterized by the dissolution of pulsed-laser ablated species into a liquid flux layer placed on the film/substrate surface and the crystallization of supersaturated species into the solid film under a quasi-equilibrium state between the growing film and the liquid flux.…”
Section: Introductionmentioning
confidence: 99%
“…PLD is one of the well-known vapor phase deposition processes for fabricating ceramics and metallic thin films. We have enabled to fabricate multi-component metallic and ceramics thin films just by ablating a stoichiometric target placed in vacuum chamber with KrF excimer laser [9]. The prepared thin film sample can be trans- ferred to the LM system without exposing it to air so that serious oxidation of metallic thin films is evitable.…”
Section: Introductionmentioning
confidence: 99%